Genomic insights into the glutathione S-transferase gene family of two rice planthoppers, Nilaparvata lugens (Stål) and Sogatella furcifera (Horváth) (Hemiptera: Delphacidae). - Wen-Wu Zhou (Public Library of Science (PLoS), 2013)
Background Glutathione S-transferase (GST) genes control crucial traits for the metabolism of various toxins encountered by insects in host plants and the wider environment, including insecticides. The planthoppers Nilaparvata lugens and Sogatella furcifera are serious specialist pests of rice throughout eastern Asia. Their capacity to rapidly adapt to resistant rice varieties and to develop resistance to various insecticides has led to severe outbreaks over the last decade. Methodology/principal findings Using the genome sequence of N. lugens, we identified for the first time the complete GST gene family of a delphacid insect whilst nine GST gene orthologs were identified from the closely related species S. furcifera. Nilaparvata lugens has 11 GST genes belonging to six cytosolic subclasses and a microsomal class, many fewer than seen in other insects with known genomes. Sigma is the largest GST subclass, and the intron-exon pattern deviates significantly from that of other species. Higher GST gene expression in the N. lugens adult migratory form reflects the higher risk of this life stage in encountering the toxins of non-host plants. After exposure to a sub-lethal dose of four insecticides, chlorpyrifos, imidacloprid, buprofezin or beta-cypermethrin, more GST genes were upregulated in S. furcifera than in N. lugens. RNA interference targeting two N. lugens GST genes, NlGSTe1 and NlGSTm2, significantly increased the sensitivity of fourth instar nymphs to chlorpyrifos but not to beta-cypermethrin. Conclusions/significance This study provides the first elucidation of the nature of the GST gene family in a delphacid species, offering new insights into the evolution of metabolic enzyme genes in insects. Further, the use of RNA interference to identify the GST genes induced by insecticides illustrates likely mechanisms for the tolerance of these insects.